Identifikasi gula spesifik pada aglutinin dari rumput laut - Jenny Kumajas; Soenandar Millian Tompunu Tengker (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
Agglutinin or lectin is a protein or glycoprotein that binds saccharide specifically. The substance can agglutinate cells, because of the cells surfaces consist of saccha- rides. Halymenia durvillaei, Laurencia obtusa and Ulva fasciata, contain agglutinin. Cells agglutination by agglutinin can be inhibited by specific saccharide which is its specific sugar. This research aims to determine the specific sugar of agglutinin from Halymenia durvil laei, Laurencia obtusa and Ulva fasciata seaweeds. The researched shows that specific sugar on agglutinin of Laurencia obtusa is D-Glucosamine, and Ulva fasciata is D(+)-Glucose.